First draft of proposals to break the deadlock in agricultural negotiations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The first draft of a paper (the 'Harbinson paper') setting out a basis for...